TINJAUAN YURIDIS TERHADAP GELANGGANG PERMAINAN BERDASARKAN PERATURAN DAERAH NOMOR 3 TAHUN 2003 TENTANG KEPARIWISATAAN DI KOTA BATAM - Nehe, Idialman (SCIENTIA JOURNAL, 2019)
The State of Indonesia is a state of law based on Pancasila and the Constitution of the Republic of Indonesia which guarantees the rights of individuals, groups and upholds regional rights according to their respective regions. Batam city is an autonomous region that has the right to regulate and make Regional Regulations, one of which is the Regional Regulation on Tourism, namely the Mechanical / Electronic Game Center. The main function of the game is limited to entertainment venues. But actually in the field, it is often used as a means of gambling by managers / entrepreneurs. The violation collided regulations and with the laws, one of which is the Criminal Code (KUHP).The Criminal Code regulates, distinguishes criminal sanctions from managers / entrepreneurs and gambling players. Based on this, legal uncertainty arises which violates the principle of legal certainty in Indonesia when the decision is not in accordance with the Laws and Regulations, the government should only be guided by the written legislation, because the government (Judge) is only a mouthpiece of the Act.